Resultados preliminares de um estudo qualitativo sobre a interação entre mãe e criança desnutrida grave, no contexto da hospitalização Preliminary results of a qualitative study of interaction between mothers and seriously malnourished hospitalized children - Marisa Amorim Sampaio; Ana Rodrigues Falbo; Maria do Carmo Camarotti; Maria Gorete Lucena de Vasconcelos (Instituto Materno Infantil de Pernambuco, 2007)
OBJETIVOS: analisar elementos da psicodinâmica interativa entre mães e crianças desnutridas graves hospitalizadas. MÉTODOS: método qualitativo baseado no referencial psicanalítico, com entrevistas semi-estruturadas, observações e filmagens. Empregou-se a análise de conteúdo, elegendo-se temas representativos. RESULTADOS: foram acompanhadas oito díades de crianças entre seis e 18 meses de idade e a mãe biológica, internadas no Instituto Materno Infantil Prof. Fernando Figueira-IMIP, em Recife, Pernambuco. Identificaram-se três temas, os quais ilustram o processo de parentalidade, sua importância na psicodinâmica interativa da díade, fatores que podem ter interferido na construção/ruptura do vínculo, sua contribuição para a situação de desnutrição e expressão na hospitalização. CONCLUSÕES: a partir da análise preliminar, reforça-se a influência mútua de mãe e filho na construção da interação e a complexidade dos distúrbios funcionais, sugerindo que estados extremos de desnutrição podem estar associados a faltas e/ou falhas nutricionais, bem como a vivências de privação ou excesso psicoafetivo. A observação da interação mãe-criança em momentos críticos, como desnutrição e hospitalização, pode auxiliar a família e a equipe de saúde na compreensão do processo de adoecimento e da necessidade do atendimento integral. OBJECTIVES: to analyze the features of the interactive psychodynamics of the interaction of mothers with seriously malnourished hospitalized children. METHODS: qualitative research based on psychoanalysis, using semi-structured interviews, observations and video recordings. Content analysis was applied to representative topics. RESULTS: a study was conducted of eight pairs consisting of a biological mother and seriously malnourished child aged between six and 18 months of age hospitaized at the Instituto Materno Infantil Prof. Fernando Figueira-IMIP, in the city of Recife, State Pernambuco, Brazil. Three central topics were identified, illustrating the process of becoming a parent, its importance for interactive psychodynamics, factors that interfere in the formation/rupture of the mother-child bond, its repercussions on the situation of malnutrition and the way it manifests itself in a context of hospitalization. CONCLUSIONS: from the preliminary analysis, the mutual influence of the mother and the child on the construction of the interaction and the complexity of the functional disharmonies is reinforced, suggesting that extreme states of malnutrition may be associated to nutritional privation and/or errors, as well as the experiences of psycho-affective privation or excess. The observation of mother-child interaction at critical moments, such as malnutrition and hospitalization, may help family and health professionals to understand how the illness develops, and suggest the need for integrated health care.